Association of low‐activity ALDH2 and alcohol consumption with risk of esophageal cancer in Chinese adults: A population‐based cohort study - Yu, C; Guo, Y; Bian, Z; Yang, L; Millwood, I; Walters, R; Chen, Y; Chen, Y; Zhang, X; Lei, Y; Chen, J; Chen, Z; et al. (Wiley, 2018)
Existing evidence remains inconclusive as to how the association between inactive ALDH2 and esophageal cancer (EC)depends on alcohol consumption. The study is based on the China Kadoorie Biobank cohort, with 10 years follow-up of 0.5million adults aged 30–79 years. ALDH2 activity was assessed by both self-reported flushing response and Glu504Lys(rs671 G>A) polymorphism. Among both male and female participants who consumed alcohol less than weekly(n569,519; 211 EC cases), low active or inactive ALDH2 was not associated with increased EC risk [HRs (95% CIs): GAvs.GG 0.75 (0.54, 1.04); AAvs. GG 1.01 (0.46, 2.20)]. Among male weekly alcohol consumers, both flushing response[n559,380; 501 EC cases; HRs (95% CIs): “soon after drinking”vs. “no” flushing response 1.45 (1.05, 2.01)] and rs671[n510,692; 94 EC cases; GAvs. GG 3.31 (1.94, 5.67)] were associated with EC risk. The increased EC risk associated with“soon” response or rs671 GA was apparent in men consuming alcohol≥30g/d. Among male daily consumers, the HRs(95% CIs) for EC associated with 15g/d of alcohol were 1.28 (1.15, 1.44) for “soon” response [vs. other responses: 1.12(1.09, 1.15);pinteraction50.047;n536,401, 425 EC cases] and 1.41 (1.08, 1.82) for rs671 GA [vs. GG: 1.16 (1.06, 1.27);pinteraction50.493;n56,607, 80 EC cases]. Self-reported flushing response had low sensitivity (56.8%) and high specificity(88.4%) in identifying rs671 A allele among male weekly alcohol consumers. In conclusion, low-activity ALDH2 was associ-ated with increased EC risk among male heavy alcohol consumers. More accurate measurement of alcohol-related EC riskallows better achievement of precision prevention.